The effects of marihuana on specific cardiovascular parameters during exercise - Dosch, Margaret F. (My University, 1975)
The study was conducted to exmine potential long term ef--ectu of marihuana upon the cardiovascular system before, duling, and after submaximal exercise. TRe following specific s=diovascular parameters were used to compare long term marihuana users to non-users, 1) Resting heart r a t e and blood pressure 2) Exercise heart rate, blood pressure, and ECG cha~ges 3) Immediate post-exercise heart rate, blood pressure, and ECG changes a t two, four, and six minute intervals 4) Time on the treadmill to reach the exercise level of the target heart rate, The two samples consisted of 23 computer matched pairs Bekwaen the ages of 17 and 21, The subjects were solicited frm the Personal Health and General Psychology classes offered i n the curriculum at: the University of Wisconsin-La Crosse, The screening and testing procedures were conducted over a g e ~ i o de f two marther. 'Phe statiatieal. male1 used i n t h i s study was the paired t @eat. The five percent level of confidence was the c r i t i c a l s t ~ t i s t i c a lv alue ehoeen f o r acceptance or r e j e c t i o n of the nuLL hypathesls, Significant differences between the marihuana users and nen-users were found i n heart rate and d i a s t o l i c blood pressure during the post-exercise periodo The users' heart rate was significantly lower than the non-users a t four minutes past exercise. A t four and six minutes post exercise the users' diastolic bl-d prsss8=e was significantly higher than the non-users. There were no signifacant long term effects of marihuana on the resting cardiovascular parameters. The long term use of marihuana does not r e s u l t i n any apparent ECG changes.
Keywords: Heart beat; Marijuana - Physiological effect